A re-interpretation of the Levens Park ring cairn, Cumbria, based on the original excavation archives. Issue 2 (3rd July 2021) - Clare, Tom; Cook, Geoff; Hodkinson, Ian D.; Simpson, Mark; Read, Stephen
ABSTRACT: The site of a Beaker burial excavated in Levens Park, Cumbria was published by David Sturdy in 1972 as that of a farmstead or place for the living altered into a ring cairn or place for the dead. However, the recent discovery of the excavation archive and contemporary correspondence reveals a far more complex monument than previously understood. We draw attention to a series of important omissions from the excavation report, provide a detailed account of the excavated monument and seek to create a new narrative regarding its development and purpose. We argue that the monument was built as a series of changing structures and demonstrates the idea of monuments in progress and, thereby, the creation of communal memory and identity. The absence of a full report of this excavation means that its wider significance has remained unknown. It represents one of the earliest examples of what Sturdy called 'rescue archaeology' and demonstrates a complex sequence of structural components and burial that contributes to our understanding of the Early Bronze Age. The broader archaeological appraisal of Levens Park, which provided the context for this excavation, represents one of the earlier examples of landscape archaeological survey in Britain.